The Effectiveness of RUBIC Interactive Games in Improving Early Childhood Numeracy and Grouping Skills - Syafiqoh, Aisyatus; Haryono (Journal of Education and Religious Studies, 2025)
Early childhood cognitive development can be optimally enhanced through engaging and interactive learning media. This study examines the effectiveness of RUBIC (Ruang Belajar Interaktif Numeric), an interactive educational game, in improving counting and categorizing skills among young children. This research employed a quantitative approach with a one-group pre-test and post-test experimental design. The participants comprised 15 children from Group B at TK Saraswati during the even semester of the 2024/2025 academic year. Data were collected through observation, documentation, and tests, using pre-test and post-test items and observation sheets as instruments. The data were analyzed using the Wilcoxon Signed-Rank Test and normalized gain (N-Gain) analysis. The results showed significant improvement after implementing the RUBIC game (p = 0.001). The average counting score increased from 64.7% to 97.8%, while the categorizing score rose from 66.1% to 99.2%. The N-Gain values for counting and categorizing were 0.4277 and 0.4093, respectively, falling into the moderate improvement category. These results demonstrate increased learning achievement levels from "adequate" to "very high." However, the study is limited by its small sample size and the absence of a control group. Future research is recommended to involve a larger sample and a more robust experimental design to validate and expand upon these findings.